The Development and Validation of the GMOAS, an Instrument Measuring Secondary School Students' Attitudes Towards Genetically Modified Organisms - Herodotou, Christothea; Iolie Nicolaidou; Hadjichambis, Andreas Ch.; Kafouris, Dimitris; Terzian, Frederiki; Kyza, Eleni A. (My University, 2012)
Genetically modified organisms (GMOs) is a rapidly evolving area of scientific innovation and an issue receiving global attention. Attempts to devise usable instruments that assess people's attitudes towards this innovation have been rare and non-systematic. The aim of this paper is to present the development and validation of the genetically modified organisms attitudes scale (GMOAS), an instrument measuring secondary school students' attitudes towards GMOs. The responses of 1,111 secondary school students from Cyprus were used to validate the instrument. Principal component analysis with varimax rotation revealed a clear three-factor solution explaining 45.8% of the total variance. The factors underlying the attitudes' construct are: GMO implications on health, Interest in the topic of GMOs, and GMO implications on the environment. The 16-item, five-point Likert-type GMOAS showed satisfactory internal consistency and discriminant validity. When the instrument was used to analyse data from Cyprus, results revealed that Cypriot secondary school students have rather non-supportive attitudes towards the cultivation and use of GMOs. Male students were less negative in using GMOs for health and environmental purposes than females. Females, however, were found to be more interested in learning about GMOs. These findings comply with the rather country-specific nature of GMO attitudes.
Keywords: GMOs; Attitudes; Biotechnology education; Assessment